Significance of out-of-plane electronic contributions in Bi-cuprates studied by resonant photoelectron spectroscopy at the Cu2p edge. (6th March 2018) - Janowitz, Christoph; Schmeißer, Dieter
Abstract: In high-temperature superconductors with a layered crystal structure, the copper–oxygen planes are commonly considered to dominate the electronic properties around the Fermi energy. As a consequence, out-of-plane contributions are often neglected in the description of these materials. Here we report on a resonant photoemission study of Pb0, 4 Bi1, 6 Sr2, 0 CaCu2 O8 ((Pb, Bi)-2212) and Pb0, 6 Bi1, 4 Sr1.5 La0.5 CuO6 ((Pb, Bi)-2201)) single crystals to unravel the resonant decay mechanisms at the Cu2p absorption edge. We find evidence for a pronounced polarization dependence caused by two different Auger processes for in-plane and out-of-plane orientations. We deduce that the lowest energy valence state—which is involved in the two Auger processes—consists of three-dimensional contributions by admixed out-of-plane Sr, Bi, and O2p states. It also suggests that the doping-induced charge density is dynamic, fluctuating within the Cu–O plane, and spills out perpendicular to it. This suggests that out-of-plane electronic degrees of freedom should be included in future consistent theoretical models of these materials.